PENYEBUTAN DAN PENGGUNAAN H}ADI>>>N: Sudut Pandang Kajian H}adi>th Warga NU Desa Gadingmangu Kecamatan Perak Kabupaten Jombang - Khamim Khamim (Dialogia, 2019)
Abstract: This article scrutinize the habits of '(Nahd}iyyi>n) people in Gadingmangu Village, Perak District, Jombang Regency, related to the meaning of h}adi>th. Besides the NU community, LDII people who have more or less different points of view in the study of h}adith in this area. Consequesntly, Nahd} iyyi> n community in this region has considerable responsibility in delivering hadith studies to their next generation. This studyindicsted that in the way to declare hadith, the people of Nahd}iyyi>n are accustomed to mention the first narrator / final sanad, the narrator of the h}adi>th (Rasu> l Alla> h), and matn of hadith in Arabic speaking or even only with translations from matn. They frequently refer to the statement "al-h}adi>th aw kama> qa>l". Furthermore, the declaration of hadith is often derived from the books of fiqh and it isn’t from the books of hadith. In terms of the understanding of h}adi>th, Nahd} iyyi> n people are accustomed to starting by explaining the meaning of vocabulary, followed by the meaning of short sentences. The translation of the matn of  hadith is mostly done by the tafsi tarjamat model> riyyah. The content of the hadith is briefly explained, then the related verses of the Qur'an and other h}adi>th are referred. The sharh} al-h} adi are rarely used> th in understanding the hadit, and i’s usage is directed as a reinforcement of ta'bi> r. It is occurred due to  the limited knowledge of the community regarding the hadith and their belief in the books of the ulama '.الملخص: يتناول هذا البحث عادات نهضة العلماء (النهضيين) في قرية Gadingmangu، Perak، Jombang Regency، في تفسير الحديث. بجانب مجتمع نهضة العلماء، توجد فرقة المجتمع LDII لديهم وجهات النظر المختلفة في دراسة الحديث. ولهذا السبب، للنهضيين عاتقها مسؤولية كبيرة في نقل دراسات الحديث إلى جيلهم القادم. تتضح هذه الدراسة أنه فيما يتعلق بذكر الحديث، اعتاد أهل النهضة أن يذكروا الراوي الأول/سند النهائي ، راوي الحديث (رسول الله) ، ومتن الحديث باللغة العربية أو ترجمة المتن. وهم يشيرون أيضًا إلى العبارة "الحديث أو كما قال". لا يكتفى إلى هذا الحد، فذكر الحديث في كثير من الأحيان لا يستمد على كتب الحديث بل من كتب الفقه. ومن حيث فهم الحديث، اعتاد النهضييون بشرح معنى المفردات ثم الجمل القصيرة. تتم ترجمة متن الحديث في الغالب بالترجمة التفسيرية. ويتم شرح محتوى الحديث باختصار، ثم ترتبط آيات القرآن والحديث الآخر. في فهم الحديث، يقل استخدام كتب شرح الحديث. من حيث استخدامه، يتم توجيه الحديث المدرسي كتعزيز للتعبير. وهذا بسبب معرفة لمجتمع المحدودة بالحديث واعتقادهم بكتب العلماء.Abstrak: Artikel ini mengkaji kebiasaan masyarakat Nahdlotul Ulama’ (Nahd}iyyi>n) Desa  Gadingmangu Kecamatan Perak Kabupaten Jombang, terkait dengan pemaknaan mereka terhadap h}adi>th . Disamping masyarakat NU, di daerah ini juga terdapat masyarakat LDII yang sedikit banyak memiliki perbedaan sudut pandang dalam kajian h}adi>th. Karena itu, Nahd}iyyi>n di wilayah ini memiliki tanggung jawab yang cukup besar dalam mewariskan kajian-kajian h}adi>th  kepada generasi penerus mereka. Kajian ini menunjukkan bahwa dalam hal penyebutan h}adi>th , masyarakat Nahd}iyyi>n terbiasa menyebutkan periwayat pertama/sanad akhir, nara sumber h}adi>th (Rasu>l Alla>h), dan matn h}adi>th  yang berbahasa arab atau bahkan hanya dengan terjemahan dari matn. Biasanya mereka juga menyebut pernyataan “al-h}adi>th aw kama> qa>l”. tidak hanya itu, penyebutan h}adi>th tidak jarang bersumber dari kitab-kitab fiqh, bukan dari kitab h}adi>th . Dari segi penggunaannya, h}adi>th  yang dikaji diarahkan sebagai penguat terhadap ta’bi>r. Ini terjadi karena keterbatasan pengetahuan masyarakat terkait dengan h}adi>th  dan kepercayaan mereka terhadap buku-buku karya para ulama’.